Elevated factor VII as a risk factor for recurrent fetal loss - Miller, Connie H.; De Staercke, Christine; Benson, Jane; Hooper, Craig W.; Dilley, Anne; Evatt, Bruce L.; Benito, Carlos; Patterson-Barnett, Anne; Eller, Daniel; Philipp, Claire S. (Thrombosis and Haemostasis, 2005)
Haemostatic abnormalities can be detected in a portion of the women who have recurrent fetal loss. We measured factor VII coagulant activity (FVII:C) in 65 women with 3 or more fetal losses (recurrent cases), 31 women with one 2nd or 3rd trimester loss (late loss cases), and 81 women with only live births (controls). FVII:C was greater than 2 standard deviations above the mean for controls in 9 recurrent cases (13.8%) and 2 controls (2.5%) for an odds ratio of 6.35 (95% CI 1.32–30.52, p=0.012). In recurrent cases, mean levels were significantly higher than controls for FVII:C (p=0.003), FVII antigen (p=0.024), and FVIIa (p=0.001). Late loss cases had an odds ratio of 4.23 (95% CI 0.67–26.67, p=0.098) with FVII:C, FVII antigen, and FVIIa not significantly different from the controls. DNA was examined for the presence of mutations or polymorphisms in the promoter region of the FVII gene, using denaturing HPLC. Abnormal patterns were confirmed with direct sequencing. A previously reported polymorphism,–402 G>A, was found to be present in 11/14 subjects with elevated FVII:C (79%) and 43% of those with normal levels (p=0.029). FVII:C, FVII antigen and FVIIa varied significantly with genotype; however, genotype frequencies did not differ between controls and either case group. No other promoter polymorphisms were identified. This is the first report of a significant elevation of FVII in a population with recurrent fetal loss. These data suggest the need for further investigation of this potential risk factor.
Keywords: Factor VII; factor VII polymorphisms; fetal loss; recurrent fetal loss